2020
DOI: 10.1007/s11698-020-00210-5
|View full text |Cite
|
Sign up to set email alerts
|

Inequality and conflict as drivers of cooperation: the location of wine cooperatives in pre-1936 Spain

Abstract: As it is usually believed that cooperatives made a great contribution to the modernisation of agriculture and when they began to spread agriculture still had a great weight in European economies, it is of interest to know why agricultural cooperatives had uneven success, both from one crop to another and between and within countries. In this article, I focus on the intriguing case of wine, a product of great importance to Mediterranean Europe. After defending that, in actual fact, wine cooperatives were genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…D' aquesta manera s'han aconseguit resultats extraordinaris en l'increment en la qualitat i el valor afegit dels seus productes, cosa que s'ha traduït en un gran creixement de les seves vendes i especialment de la seva comercialització en determinats segments dels mercats internacionals. éxito de Miquel y Costat & Miquel (siglos xviii-xxi) (2016, darrerament també publicat en anglès)� Ha estat editor de Revista de Historia Industrial (2012-2021.…”
Section: Discussionunclassified
“…D' aquesta manera s'han aconseguit resultats extraordinaris en l'increment en la qualitat i el valor afegit dels seus productes, cosa que s'ha traduït en un gran creixement de les seves vendes i especialment de la seva comercialització en determinats segments dels mercats internacionals. éxito de Miquel y Costat & Miquel (siglos xviii-xxi) (2016, darrerament també publicat en anglès)� Ha estat editor de Revista de Historia Industrial (2012-2021.…”
Section: Discussionunclassified
“…Although the number of cooperatives in relation to the number of enterprises, in general, is very small, there is still a lot of attention to cooperatives as an alternative organizational form (Boone & Özcan, 2014). The cooperative model has been regarded as the most appropriate to envelop the needed modernization of agriculture and its integration into the market (Ndongala, 1966;Garrido, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Samuel Garrido (2014), however, argues that social capital does not necessarily lead to the emergence of cooperatives, as shown by the citrus-growing cooperatives in eastern Spain. In fact, it has been recently suggested that wine cooperatives emerged in (a part of) Catalonia as a result of the unequal distribution of land and the ensuing political and social conflics (Garrido, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In economic history, several studies have recently explored the formation and development of cooperatives, broadly defined as organisations where profits or benefits are shared by their members (Henriksen et al 2012;Beltrán 2012;Martínez-Soto et al 2012;Garrido 2014Garrido , 2020Fernández 2014a;Fernández and Simpson 2017;Watts 2017;among others). Yet, little attention has been paid to the spatial dimension which, in turn, raises a relevant question.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation